Golput Pasca Orde Baru: Merekonstruksi Ulang Dua Perspektif - - Nyarwi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
The non-voter phenomenon has been generating the controversial perspectives from The New Order to the Post-New Order. This paper discusses two important things: the non-voter based on the political movement perspective and political behavior perspective. First, the non-voter phenomenon has been capitalized by political actors as a political instrument to oppose the political regime. Second, according to political behaviorist science perspective, the non-voter has been analyzing as part of political behavior in national or local election event.